CORRELATION BETWEEN HEIGHT, BMI, MUAC WITH ANEMIA STATUS IN ADOLESCENT GIRLS - Muminah; Budi Amalia , Rize; Sudaryanti , Lestari; Sulistiawati, Sulistiawati (UNIVERSITAS AIRLANGGA, 2024)
Background: Anemia in adolescents is a health problem that needs immediate intervention in Indonesia. Anemia can caused by malnutrition. protein and iron deficiency will cause nutritional problems including stunted, thinness, and Mid Upper Arm Circumference (MUAC) < 23,5 cm. Protein and iron deficiency can interfere with the formation of hemoglobin resulting in anemia. This study aims to analyze the relationship between status based on height, Body Mass Index (BMI) and MUAC with anemia status at Mambaus Sholihin Islamic Boarding School in Gresik Regency. Method: This research is a quantitative observational analytic with the cross sectional method. The population was adolescent girls in Mambaus Sholihin Islamic Boarding School in Gresik Regency. The sample was 11th and 12th grade senior high school girls with a total of 141 respondents using the total sampling technique. The variables used in this research consisted of height, BMI, MUAC, and anemia. Height data was obtained by using microtoise, BMI using microtoise and scales, MUAC using tape measure plastic, and hemoglobin using the digital tool of Point of Care Testing (POCT) method. The research data were analyzed by chi square test with a contingency coefficient of 95%. Result: The results showed that out of 141 adolescent girls, 66.7% had normal height status, 23.4% were stunted, and 9.9% were severely stunted. In BMI status, 55.3% normal, 14.9% thinness, 15.6% overweight, and 14.2% obese. MUAC status was 79.4% with MUAC â‰¥ 23.5 cm and 20.6% with MUAC < 23.5 cm. Anemia status was 51.8% frail and 48.2% not anemic. After the chi square test, the significance value was obtained (p=0.006), which means that statistically there was a significant relationship between height and anemia, (p=0.003) there was a significant relationship between BMI and anemia, and (p=0.01) there was a significant relationship between MUAC and anemia. Conclusion: There is a relationship between nutritional status based on height, BMI, and MUAC with anemia status in adolescent girls at Mambaus Sholihin Islamic Boarding School in Gresik Regency.